2021
DOI: 10.2217/fmb-2021-0150
|View full text |Cite
|
Sign up to set email alerts
|

Management of Chronic Pseudomonas Aeruginosa Infection with Inhaled Levofloxacin in People with Cystic Fibrosis

Abstract: People with cystic fibrosis (CF) are highly susceptible to bacterial infections of the airways. By adulthood, chronic Pseudomonas aeruginosa ( Pa) is the most prevalent infective organism and is difficult to eradicate owing to its adaptation to the CF lung microenvironment. Long-term suppressive treatment with inhaled antimicrobials is the standard care for reducing exacerbation frequency, improving quality of life and increasing measures of lung function. Levofloxacin (a fluoroquinolone antimicrobial) has bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 87 publications
0
13
0
Order By: Relevance
“…The resistome has an impact on the phenotypic antibiotic bacterial resistance, which is also affected by lung environment factors such as airway mucus composition, biofilm formation, bacterial interactions, human genetics and the immune response. [16,[20][21][22]] Continuous daily administration mode also increasingly recommended [23] Maintenance therapy Proposition of 6 months of oral azithromycin with a 3 times a week dose of 500 mg [27] Key pathogens Antibiotic courses administered 3 times per week [24]…”
Section: Influence Of Macrolides On the Respiratory Microbiomementioning
confidence: 99%
“…The resistome has an impact on the phenotypic antibiotic bacterial resistance, which is also affected by lung environment factors such as airway mucus composition, biofilm formation, bacterial interactions, human genetics and the immune response. [16,[20][21][22]] Continuous daily administration mode also increasingly recommended [23] Maintenance therapy Proposition of 6 months of oral azithromycin with a 3 times a week dose of 500 mg [27] Key pathogens Antibiotic courses administered 3 times per week [24]…”
Section: Influence Of Macrolides On the Respiratory Microbiomementioning
confidence: 99%
“…Clinical trials have demonstrated a significant improvement in lung function and a reduction in the exacerbation rate with inhaled levofloxacin against placebo [ 16 , 17 ] and equivalent outcomes compared with tobramycin in adult patients with CF [ 18 ]. Levofloxacin belongs to the fluoroquinolone antibiotic class and displays broad-spectrum activity against Gram-negative and Gram-positive bacteria, disrupting the bacterial DNA synthesis through inhibitory interactions with the DNA gyrase and topoisomerase IV enzymes [ 5 , 19 ]. The efficacy spectrum and mechanism of action of levofloxacin are different from the previously approved inhaled antipseudomonal antibiotics (tobramycin, colistin, and aztreonam).…”
Section: Discussionmentioning
confidence: 99%
“…Once that bacterial colonisation with Pseudomonas aeruginosa is established, complete eradication is difficult to achieve [ 3 ], and the disease progresses to a state of chronic infection with concomitant inflammation and lung remodelling that produces structural changes and progressive, life-threatening deterioration of lung function [ 4 ]. Pseudomonas aeruginosa infections are predominant in adulthood and are a major cause of morbidity and mortality in people with CF [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations